Recollecting Cross-Cultural Evidences: Are Decision Makers Really Foresighted in Iowa Gambling Task? - Lee, We-Kang; Lin, Ching-Jen; Liu, Li-Hua; Lin, Ching-Hung; Chiu, Yao-Chu (Frontiers in Psychology, 2020)
The Iowa Gambling Task (IGT) has become a remarkable experimental paradigm of dynamic emotion decision-making. In recent years, research has emphasized the “prominent deck B (PDB) phenomenon” among normal (control group) participants, in which they favor “bad” deck B with its high-frequency gain structure—a finding that is incongruent with the original IGT hypothesis concerning foresightedness. Some studies have attributed such performance inconsistencies to cultural differences. In the present review, 86 studies featuring data on individual deck selections were drawn from an initial sample of 958 IGT-related studies published from 1994 to 2017 for further investigation. The PDB phenomenon was found in 67.44% of the studies (58 of 86), and most participants were recorded as having adopted the “gain-stay loss-randomize” strategy to cope with uncertainty. Notably, participants in our sample of studies originated from 16 areas across North America, South America, Europe, Oceania, and Asia, and the findings suggest that the PDB phenomenon may be cross-cultural.